Utilização de heterociclos 1,2,3-triazólicos para a retenção e recuperação de corpos hídricos contaminados com metais - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Although most of the treatment and disposal processes of domestic or industrial residues have strict environmental safety protocols, unfortunately, there is always a marginal loss during their processes, which can cause environmental contamination, either by water, gas or dry means. In this way, allowing these pollutants of the most diverse levels of contamination to escape into nature, from residues of low environmental impact to chemical compounds, often containing heavy metals, which are extremely toxic and can cause irreversible dameges to the local fauna and flora, besides uselessness of the soil. In order to progressively reduce the environmental impacts from domestic and industrial development, there has been a significant increase in practices for the prevention and recovery of the environment over the past decades. In view of the above, the present study has as its main objective the development of a technique for the decontamination of metals in water resources by the complexation reaction between an organic ligand and metal centers. It is intended, in the future, to use this technique for the restoration or treatment of water bodies. The work methodology is centered on experimental research on the complexation reaction between the triazole ligand and the metal centers: Cu (II), Fe (III) and Pb (II). Finally, the research determined the remaining metals in solution. It was sought to obtain six metal complexes of the 1,2,3-triazole ligand with Cu2+, Pb2+ e Fe3+ ions with low water solubility at pH 5 and 7, but obtaining a probable metal complex of the ligand and the ferric ion at pH 7.
Keywords: Poluente; Descontaminação; Metais pesados; Recursos hídricos; Complexação; Cobre; Ferro; Chumbo; Pollutant; Decontamination; Heavy Metals; Water Resources; Complexing; Copper; Iron; Lead; CNPQ::CIENCIAS EXATAS E DA TERRA